Analisis Permasalahan Inflasi Dalam Sektor Keuangan Syariah di Indonesia - Cindy, Cindy Rama; Yarham, M. (Studia Economica : Jurnal Ekonomi Islam, 2023)
This journal reviews the problem of inflation in the Islamic financial system. Inflation is a general and continuous increase in the prices of goods and services over a certain period of time. An increase in the price of just one or two goods cannot be called inflation unless the increase spreads or results in an increase in the prices of other goods. This research aims to find out whether inflation has an effect on the economy in Indonesia, and what factors influence the occurrence of inflation. The type of method in this writing is qualitative. The research data instrument is secondary data which is publication data that has been collected by other parties.